Estabelecimento "in vitro" de Citronela de Java (Cymbopogon winterianus Jowitt) - Chaves, Elisiane Inês Dall'oglio (2006)
Citronella of Java (Cymbopogon winterianus Jowitt) is an aromatical plant with large usage in the manufacture of mosquito repellents because it contains essential oil rich in citronelal. The application of tissue culture on a large scale in medicinal plants production has increased significantly, since the conventional methods of propagation limit the potential use of some plants. Due that, one citronella of Java protocol was established with the objective of getting an alternative technique for the propagation of that culture. Four experiments ware conducted to evaluate the asepsis time, the explant type, the effect of vegetal regulators on the "in vitro" propagation of citronella of Java, as well as the micro-propagated seedling acclimatization. The gotten results had disclosed that the use of sodium hypochlorite (0.5%) during 30 minutes promoted a satisfactory asepsis index. The shoot tips explants type showed greater potential for the ?in vitro? development. It was verified that the use of benzilaminapurine (BAP) cytokynin is indispensable to succeed in the citronella of Java "in vitro" establishment, being able to be used in the concentration of 2.0 mg L-1. However, the use of indolbutyric acid (IBA) in the different tested concentrations did not present any results that justify its use, neither in the citronella of Java multiplication nor in the root establishment. The root establishment was evidenced when micro-propagated seedlings had been inoculated only in MS culture medium. It was verified that the check (without vegetal regulator) had a direct organogenesis, while such event was not verified in the other treatments. In the micro-propagated seedling acclimatization it was verified that the use of the floating method, it was essential for the seedlings survival, resulting in high survival index